Literature Review: Factors Influencing Purchasing Decisions in the Service Industry - Umpusinga, Hasrun Afandi; Warganegara, Tri Lestira Putri; Alam, Iskandar Ali; Habiburrahman, Habiburrahman; Barusman, Andala Rama Putra (University of Darussalam Gontor, 2024)
This research focuses on the factors that interact with each other and influence consumers' purchasing decisions, as well as how implementing effective marketing strategies can influence these decisions across various industry sectors. The purpose of the study is to examine studies that are relevant to purchase decisions, this study uses a qualitative method with a systematic literature study approach, which is an assessment and analysis of previous research related to purchase decisions, using the keywords